68Ga-PSMA PET/CT: joint EANM and SNMMI procedure guideline for prostate cancer imaging: version 1.0 - Fendler, Wolfgang; Eiber, Matthias; Beheshti, Mohsen; Bomanji, Jamshed; Ceci, Francesco; Cho, Steven; Giesel, Frederik L.; Haberkorn, Uwe; Hope, Thomas A.; Kopka, Klaus; Krause, Bernd J.; Mottaghy, Felix M.; et al. (European journal of nuclear medicine and molecular imaging, 2017)
The aim of this guideline is to provide standards for the recommendation, performance, interpretation and reporting of 68Ga-PSMA PET/CT for prostate cancer imaging. These recommendations will help to improve accuracy, precision, and repeatability of 68Ga-PSMA PET/CT for prostate cancer essentially needed for implementation of this modality in science and routine clinical practice.